On linearization toward a restrictive theory - Cinque, Guglielmo 1948- (The MIT Press, 2023)
"An original, theoretical work on cross-linguistic word order from a leading syntactician"--
Keywords: Wortstellung; Phrasenstruktur; Grammar, Comparative and general / Word order; Ordre des mots